Lysimachia kraduengensis (Primulaceae), a new species from northeastern Thailand - Julius, Avelinah; Tagane, Shuichiro; Naiki, Akiyo; Gutiérrez-Ortega, José Said; Suddee, Somran; Rueangruea, Sukid; Yahara, Tetsukazu; Utteridge, Timothy (Phytotaxa, 2016)
A new species of Primulaceae from Thailand, Lysimachia kraduengensis, is described and illustrated. It is morphologically similar to L. engleri, L. lancifolia, L. laxa and L. sikokiana in having solitary and axillary flowers, a yellow corolla, relatively long pedicels and basifixed anthers. The new species can be distinguished by the combination of its height, leaf texture, petiole, calyx and anther length, and brown coloration on the flowers. In addition, the conservation status, an updated key to Lysimachia species in Thailand, and discussion of the systematic placement of the new species based on the trnL-F marker of chloroplast DNA are provided.